1999
DOI: 10.1590/s0004-282x1999000500010
|View full text |Cite
|
Sign up to set email alerts
|

Idade de aparecimento e desaparecimento das pontas rolândicas em 160 crianças acompanhadas ambulatorialmente: estudo atuarial

Abstract: RESUMO -Proposta: Determinar a idade em que surgem e desaparecem as pontas rolândicas (PR) em traçados eletrencefalográficos de rotina. Método: Estudo prospectivo hospitalar, baseado em 412 eletrencefalogramas de 160 crianças que frequentaram o ambulatório de neuropediatria entre as idades de 1 e 16 anos, no período de março de 1989, a março de 1998. Usou-se o sistema 10/20 para colocação dos eletrodos. As crianças foram dividas, por idade, em quatro grupos (1 a 4; 5 a 8; 9 a 16; 1 a 16) e usou-se o método de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Among the 31 cases of EEGs showing rolandic spikes without concomitant seizures in our sample, there was a predominance of behavioral problems, most frequently ADHD, followed by headaches, which is in agreement with previous findings 29 . The presence of one child with Rett syndrome, and of another child with autism in our sample, both with concomitant rolandic spikes, is not surprising.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Among the 31 cases of EEGs showing rolandic spikes without concomitant seizures in our sample, there was a predominance of behavioral problems, most frequently ADHD, followed by headaches, which is in agreement with previous findings 29 . The presence of one child with Rett syndrome, and of another child with autism in our sample, both with concomitant rolandic spikes, is not surprising.…”
Section: Discussionsupporting
confidence: 93%
“…In our sample, sleep and awake EEGs were performed in 51.6% the cases; awake EEGs in 31.7%; and sleep EEGs in 16.7%; these results are similar to those obtained by Shinnar et al 28 . Amongst us, Borges et al 29 carried out a nine-year prospective study of 412 EEGs with rolandic spikes from 160 children with or without epilepsy. Surprisingly, 84.4% of the recordings in that prospective study were carried out in the awake state, despite the fact that the study's objective was to evaluate the natural history of rolandic spikes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The five age groups studied, two of which are related to children, took into consideration the period in which the main symptoms of idiopathic epilepsy appear 29 . In this study, a strong association between the prevalence of epilepsy and age was demonstrated.…”
Section: Discussionmentioning
confidence: 99%